Response to and Cost Effectiveness of Improved Kienyeji Chicken Fed on Maize-Substituted Sorghum-Based Rations - Manuya , Eric M.; A. Were , Beatrice; Rachuonyo , Harold A. (African Journal of Education,Science and Technology (AJEST), 2020)
Rearing improved indigenous chicken fed on locally available low cost, low tannin, sorghum based diets in the semi-arid areas of Western Kenya could address the region’s food insecurity resulting from low crop and livestock productivity. In this study, the response to and socio-economic significance of improved Kienyeji chicken fed on 4 maize substituted, sorghum-based diets was assessed. The diets had 2 varieties (V1 and V2) of sorghum substituting maize at 4 levels designated as T1 (0 %)-as a control, T2 (50 %), T3 (75 %), T4 (100 %). The eight dietary treatments (V1T1, V1T2, V1T3, V1T4, V2T1, V2T2, V2T3, and V2T4) were fed for 20 weeks to 256 birds randomly assigned into sixteen pens in 2 replicates. Nutritional values, feed intake, growth rate, survival rate, egg production and gross margins were determined. Results showed statistical differences (p<0.05) among treatments in the values for crude protein (CP) and Digestible Energy (DE). Treatment V2T3 had the highest CP content (20.49 %) while VIT2 had the lowest (15.03 %). Digestible Energy (DE) content was highest in V1T1 (3.3 Kcal/kg) while V1T4 had the lowest (2.483 Kcal/kg). There was also statistical differences (p<0.05) in the feed intake, growth response parameters, feed conversion ratio (FCR) and survival rate (SR). Treatment V1T2 (54.2g) had the highest feed intake while V1T4 (39.3 g) had the lowest. Feed intake in variety V2 rations was significantly different but lower than that of varietyV1 rations. Growers fed on the control rations (V1T1 and V1T2) had the best growth response (1219.1 g) while V1T4 (559.0 g) recorded the lowest. Treatments V2T2, V2T3 and V2T4 (961.45 g) recorded lower growth rate but were statistically similar to the control. Feed conversion ratio was highest with V1T4 (6.7) and lowest in the control (V1T1 and V2T1). Treatment V2T4 recorded the highest survival rate (94.1 %) while V1T4 had the lowest (61.3 %). The highest egg production (13.3 %) was observed in VIT1/ V2T1 while V1T4 had the lowest (0.56 %). Gross margin analysis based on feed cost showed diet V2T3 had the highest gross margin (Ksh 332.7 g) while Diet V1T4 recorded the lowest (Ksh 135.97). To optimize cost of formulation and cost of feeding without adversely affecting performance, sorghum variety V2 should be added at an optimum inclusion rate of 75 % while V1 should be at an optimum inclusion rate of 50 % in the diets.